The Problem of Formation of Long-term Investment Resources Formation in the Modern Russian Economy - Zhabin, A. P.; Volkodavova, Elena Viktorovna; Nesterenko, E. G. (International Journal of Economics and Financial Issues, 2016)
Mobilization of sufficient, long-term investment resources in the real economy is an urgent task today. Reducing the volume of investments, including due to the imposition of sanctions by Western countries, has led to a drop in production in many sectors of the economy, requiring the mobilization of domestic resources. In this connection, the article illustrates the issues of formation of long-term investment resources in the Russian economy. Special attention is paid to the fact that one of the sources of such investment is the stock market that is an alternative to bank loans. The most important entities of the stock market are the private pension funds, which functions in the scale of the national economy are not only pensions' coverage but also the investor's long-term projects coverage of financial and non-financial sectors of the economy. The article represents the analysis of the Pension Savings Fund's activities in Russia and abroad, reveals differences in organizational and legal forms of pensions and insurance, insurance reserves and investment of pension savings. The authors develop proposals to improve the efficiency of investment activity of the Pension Savings Fund, the use of which will increase confidence in the operating Pension Savings Fund, and the Russian economy will get a significant increment of the long-term investment resources. Keywords: Ð¡orporatization; Investment policy; Investment resources; Non-state pension funds JEL Classifications: G11; G22